Type 1 Diabetes Mellitus Due to COVID-19: Do We Need to Worry? - Gembong Satria Mahardhika; Azizah Fitriana Nurul Ilmi; Pugud Samodro; Dhadhang Wahyu Kurniawan (Keluwih: Jurnal Kesehatan dan Kedokteran, 2022)
Abstract—SARS-CoV-2, a Coronaviridae virus related to angiotensin-converting enzyme 2 (ACE2), is the virus that causes the COVID-19 pandemic. Diabetes mellitus is a condition that is reported to have a connection with the emergence of COVID-19. A diabetic patient has a higher risk of infection compared to other nondiabetic patients. In addition, some reports showed the possibility of infection that can stimulate diabetes in an individual without a hyperglycemia history. COVID-19 was also found to show a hyperglycemic conditions that may affect mortality. Therefore, a proper monitoring as well as management of glucose level is needed for COVID-19 patients regardless of their diabetes status, to minimize the risk of mortality and development of diabetes. The possibility of diabetes mellitus induced by COVID-19 infection is investigated in this paper, as well as the monitoring of COVID-19 patients with hyperglycemic conditions. Further investigation might be needed to confirm the relationship between COVID-19 and diabetes mellitus type 1. Keywords: diabetes mellitus type 1, sars-cov-2, insulin Abstrak—SARS-CoV-2, virus Coronaviridae yang berkaitan dengan enzim pengubah angiotensin 2 (ACE2), adalah virus yang menyebabkan pandemi COVID-19. Diabetes mellitus adalah suatu kondisi yang diyakini memiliki hubungan dengan adanya COVID-19. Pasien dengan diabetes memiliki risiko infeksi yang tinggi dibandingkan dengan pasien nondiabetes lainnya. Meskipun demikian, beberapa laporan menunjukkan kemungkinan infeksi yang dapat merangsang diabetes pada individu tanpa riwayat hiperglikemia sebelumnya. COVID-19 juga ditemukan menunjukkan kondisi hiperglikemik yang dapat menyebabkan angka kematian yang cukup signifikan. Oleh karena itu, diperlukan pemantauan serta pengelolaan kadar glukosa yang tepat untuk pasien COVID-19. Kemungkinan diabetes mellitus yang disebabkan oleh infeksi COVID-19 akan diselidiki dalam makalah ini, serta pemantauan pasien COVID-19 dengan kondisi hiperglikemik. Penelitian lebih lanjut mungkin diperlukan untuk mengetahui hubungan antara COVID-19 dan diabetes melitus tipe 1. Kata Kunci: diabetes mellitus tipe 1, sars-cov-2, insulin